PENINGKATAN KOMPETENSI PEDAGOGIK DALAM PENGAJARAN BAHASA INGGRIS UNTUK GURU SEKOLAH DASAR KECAMATAN SAGULUNG BATAM - yessie aldriani; Ance Jusmaya (ASOSIASI IDEBAHASA KEPRI, 2019)
English Skill is the most important nowadays so that this skill must be learned starting from the young age. Unfortunately, the 2013 curriculum has shown that English subject is only the internal component which is only the optional subject in an elementary school. In fact, seeing the era development, English has become the obligatory need for every level of education included Elementary school. As Li stated that the language acquisition is more effective before puberty because the human brain is is still flexible to learn many languages (Li, 2014). It means that the elementary students must have been introduced to English language. The government of Batam is aware of the importance of learning English for the elementary school students because Batam as one of the big trading cities in Indonesia must prepare the human resources which are able to speak English. However, there are many English teachers are still lack of English pedagogical competencies and for recruiting some new ones need extra budgets that can not be realized sooner. The best solution for this situation is to train the incompetent English teachers so that they are able to teach English to the elementary school competently (Post,2017). This idea has inspired the team of community service to train the elementary school teachers in Sagulung region to be the pedagogical competency of English teachers.The train has been responded by the the teachers positively and expected to be continued regularly in the future.